1992
DOI: 10.1111/j.1469-7610.1992.tb00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and Perinatal Factors and the Risk of Subsequent Referral for Hyperactivity

Abstract: Possible pre- and perinatal risk factors for subsequent referral for hyperactivity were assessed by comparing birth records of 129 referrals with the remaining 24,656 members of a geographically defined birth cohort. Relationships between the risk factors were accounted for using logistic regression methods. The significant factors were: social class, maternal age, antepartum haemorrhage, length of labour (second stage), 1-min Apgar and sex. Associations between referral for hyperactivity and the pregnancy, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
2
15
1
1
Order By: Relevance
“…Male gender has been found to be associated with increased prevalence in undercontrolled behaviour (2,12,13); this was also confirmed in our study. Male gender was also found to be associated with increased prevalence of anxious behaviour.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Male gender has been found to be associated with increased prevalence in undercontrolled behaviour (2,12,13); this was also confirmed in our study. Male gender was also found to be associated with increased prevalence of anxious behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…The male gender is known to be associated with a higher prevalence of undercontrolled behaviour, attention deficit disorder and conduct disorder (2,12,13). The female gender is more inclined toward overcontrolled behaviour (2).…”
mentioning
confidence: 99%
“…11,42,43 Such risk factors include threatened abortion, threatened preterm labor, preeclampsia, prematurity, intrauterine growth retardation, low Apgar scores, and fetal distress. 35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study. 11 Maternal preeclampsia and genitourinary tract infections have been associated with other neurodevelopmental disorders, including ADHD, 12,46 where an inflammatory cascade affecting fetal brain development has been suggested.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, our overall MZ and DZ correlations of 0.61 and -0.10 (same-sex twins) are strikingly similar to those of Goodman and Stevenson [(1989b) rmz = 0.68, rdz = -0.08 (same-sex twins) for maternally rated hyperactivity scores]. The lack of association between hyperactivity and birth complications contrasts with a previous study using the CBS (Chandola et al, 1992) where small but significant effects were detected. However, the subjects in this study consisted of singletons who had been referred, and thus sample differences may in part explain the disparate findings.…”
Section: Discussionsupporting
confidence: 57%